Identifikasi Kesesuaian Ekologi Permukiman Kampung Air Pulau Kemaro Sebagai Sumber Belajar Geomorfologi Fluvial - Susyati, Nanda Ayuliana; Disurya, Ramanata; Giyanto, Giyanto (Jurusan Geografi, Fakultas Ilmu Sosial, Universitas Negeri Semarang, 2023)
The objective of this study is to identify the ecological attributes of the settlements in Kemaro Island Water Village as well as assess their appropriateness as educational resources for geography course material on the topic of fluvial geomorphology in class X, SMA N 5, Palembang. The research employed a descriptive-qualitative approach, utilizing various methods for data collection such as interviews, observation, and documentation. The findings of the study indicate that Kemaro Island is a geographical feature characterized by its location as a bar or sediment situated within the central area of a channel or river flow. Kemaro Island exhibits ecological characteristics in the form of a distinctive Water Village, where individuals reside along the Musi riverbank. The primary occupations of the local community residing on Kemaro Island encompass fishing, diving, boat operation, and agricultural pursuits. The agricultural practitioners residing on Kemaro Island employ a method of rice cultivation that capitalizes on the tidal nature of the nearby river water. Kemaro Island exhibits considerable potential for utilization as a tourism destination. The water landscape of Kemaro Island possesses ecological characteristics that can serve as a valuable educational resource for studying fluvial geomorphology within an environmental context. Hence, it is anticipated that social studies Geography teachers could use the Kemaro Island Kampung Air area as an educational resource for social studies Geography, with the aim of enhancing students' understanding of the local environment